Enablers and barriers to prevent weight-regain post bariatric surgery - A qualitative enquiry - Billing-Bullen G; Nielsen D; Wham C; Kruger R (Elsevier Ltd, 2022)
Background Weight-regain is commonly experienced after bariatric surgery. This qualitative enquiry aimed to explore participants' self-reported enablers and barriers to prevent future weight-regain post-surgery. Methods Eligible adults were recruited at 12-months post-bariatric-surgery at Counties Manukau, Auckland. Participants were invited to attend data collection at their 18-month group nutrition-education session, and to participate in a focus group at 21-months post-surgery. Thematic analysis was used to evaluate patient experiences. Results Participants (n = 28) were mostly female (73.2 %), New Zealand European (41.5 %), and had gastric sleeve surgery (92.3 %). Five key themes emerged from the analysis: A Life Changing Health Journey - participants experienced a decrease in obesity-related comorbidities and a subsequent decrease in medications. Weight change and food intolerances impacted quality of life. Challenge of managing a New Healthy Lifestyle - financial stress, buying healthier foods and social events were new challenges, often centred on food. Changing Eating Behavior - all participants struggled managing eating behaviors. Mindset Changes - post-surgery most participants had a positive mindset, increased confidence, and feelings of happiness. However, many struggled with mindset around weight and food. A need for On-going Support - most felt under-supported and expressed a need for longer, specific follow-up care. Conclusion Post-surgery group education sessions provided participants with increased support from both health professionals and peers on the same journey, to overcome struggles such as binge eating or identifying new coping strategies. Findings provide important insights into the challenges patients with bariatric surgery face and key learnings to develop specific supports for future care practices.
(c) The Author/s
Keywords: Eating behavior; Focus groups; Life-changing; Mindset; Obesity; Ongoing support; Quality of life; Adult; Humans; Female; Male; Quality of Life; Bariatric Surgery; Obesity; Qualitative Research; Binge-Eating Disorder; Obesity, Morbid